Pengaruh Efikasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Di PT Korindo Group Jakarta Selatan - Ferryan Saputra (Jurnal Ekonomi dan Bisnis Digital, 2026)
Self-efficacy is one of the most influential aspects of self-knowledge in everyday human life because self-efficacy influences individuals in determining actions to be taken to achieve a goal, including estimates of the challenges to be faced. This study aims to determine how influential Work Efficacy and Motivation are on Employee Performance at PT. Korindo Group South Jakarta. The method used in this study uses the Structural Equation Modeling method with a sample of 31 respondents. This research is a quantitative research. The method of multiple linear regression analysis with the help of the SPSS program version 25.0. The data collection technique used was by distributing questionnaires. Based on the results of the t-test (partial), it was found that there was an influence of the Efficacy variable on the Employee Performance variable, with a calculated t value of 2.125> t_table 2.045. From the results of the t-test (partial), it was found that there was no influence of the Work Motivation variable (X2) on the Employee Performance variable, with a calculated t value of 1.793 <t_table 2.045. Efficacy and Work Motivation simultaneously had a positive and significant effect on employee performance, with a calculated F value> F table (6.256> 3.34).